Applications of Hybrid Process of Distillation-Pervapouration in Chemical Industry - Liang, Jinhua; Zhu, Hongji; Bai, Peng; Wang, Jingxian (Asian Journal of Chemistry, 2011)
The hybrid process of distillation-pervapouration as well as its current and forthcoming applications in chemical industry are introduced. Emphasis is given to economic potential analysis through costs comparison between pervapouration-based hybrid processes and traditional separation processes. Finally, the performance in pervapouration techniques is discussed and available solutions together with some optimization processes are summarized, which can be served as a reference for the further development of this technology.